Prospective Assessment of Carboxyhemoglobin and Methemoglobin Levels in Operating Room Personnel During HIPEC/Peritonectomy Compared with Standard Colorectal Surgery - Emil Kinda; Petar Matosevic; Sanda Smud Orehovec; Ivan Romic; Rudolf Radojkovic; Branko Bogdanic (Journal of Clinical Medicine, 2026)
Background/Objectives: In the operating room, surgical staff are exposed to inhalation of smoke from the combustion of tissues when using electrocautery. By introducing HIPEC/peritonectomy in the treatment of malignant neoplasms of the peritoneum, exposure to smoke is significantly increased. To adequately perform this procedure, high-power monopolar cautery is used. The aim of this study was to assess carbon monoxide exposure associated with surgical smoke generated during peritonectomy procedures and to compare it with exposure during standard colorectal resections. Methods: In this prospective observational study, a total of 360 blood samples were collected and analyzed from surgeons participating in surgical procedures. The study cohort was divided into two groups: the HIPEC/peritonectomy group and the standard resection group. Blood samples were obtained from three surgeons who participated in a total of 30 procedures, comprising 15 HIPEC/peritonectomy procedures and 15 standard resection procedures. Samples were collected at the start of the intervention, at the 20th and 40th minutes, and at the end of procedures. Results: COHb values increased over time, and levels were higher in the peritonectomy group. An increase in MetHb levels was seen in HIPEC/peritonectomy, but not in the standard colorectal resection group. The observed values did not lead to symptoms of acute CO poisoning. Conclusions: The results suggest that the use of electrocautery increases carboxyhemoglobin (COHb) and methemoglobin (MetHb) levels in surgical staff; however, these increases did not reach clinical significance. The long-term health consequences of repeated exposure to surgical smoke, as well as the effectiveness of personal protective equipment and smoke evacuation systems in reducing this exposure, should be investigated in future studies.